2021
DOI: 10.2147/nss.s317618
|View full text |Cite
|
Sign up to set email alerts
|

PTSD Symptoms and Sleep Quality of COVID-19 Patients During Hospitalization: An Observational Study from Two Centers

Abstract: Background The outbreak of COVID-19 has developed into a pandemic. Data are required that specifically address the psychological consequences in COVID-19 confirmed patients. This study mainly aimed to examine posttraumatic stress disorder (PTSD) symptoms and sleep quality among COVID-19 confirmed patients during hospitalization. Methods An observational study was conducted in two designated hospitals in Wuhan, China. Data were collected from 190 patients hospitalized wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
(75 reference statements)
2
6
2
Order By: Relevance
“…Similarly, a previous study conducted in Peru reported the prevalence for depression (12.1%), anxiety (8.4%), and PTSD (10.5%) in health care-workers during the pandemic [ 24 ]. The prevalence reported in systematics reviews indicated higher values than our study showed for depression (45%), anxiety (47%), and PTSD (16 to 22.6%) [ 4 , 69 , 70 ]. These differences among researchers could be explained due to the different socio-demographic compositions, different study designs, and measurement instruments used, which may influence the degree of prevalence.…”
Section: Discussioncontrasting
confidence: 77%
“…Similarly, a previous study conducted in Peru reported the prevalence for depression (12.1%), anxiety (8.4%), and PTSD (10.5%) in health care-workers during the pandemic [ 24 ]. The prevalence reported in systematics reviews indicated higher values than our study showed for depression (45%), anxiety (47%), and PTSD (16 to 22.6%) [ 4 , 69 , 70 ]. These differences among researchers could be explained due to the different socio-demographic compositions, different study designs, and measurement instruments used, which may influence the degree of prevalence.…”
Section: Discussioncontrasting
confidence: 77%
“…122EMJ • September 2023 • Creative Commons Attribution-Non Commercial 4.0 above, and 40.2% were engaged in full-time employment. However, the mean age of patients in a study of Sun et al19 was higher as compared with the present study (55.7±13.7 years), with…”
contrasting
confidence: 83%
“…These data are in line with part of the previous literature reporting higher levels of psychopathological symptoms in hospitalized patients regardless the disease severity and the kind of clinical treatments received. [20][21][22][23][24][25] Coherently, these findings seem to be an interesting confirmation that psychological effects are not related to the level of pulmonary involvement, rather to the illness experience itself. Although further research is needed, it is reasonable to assume that no differences were unveiled as each disease pathway has involved peculiar stressful risk factors for the individual mental health.…”
Section: Discussionmentioning
confidence: 56%
“…4 However, other studies did not find any statistically significant correlations between the illness severity and the PTSD, depressive and anxiety symptoms. [20][21][22][23][24][25] Moreover, an Italian research shown that higher risk of developing Long Covid -defined as the persistence of physical or psychological symptoms for more than four weeks after recovery from the acute phase of the disease -does not depend on the severity of the virus. 8 Therefore, further studies are needed to assess possible differences concerning psychopathological symptoms in COVID-19 patients with different disease severity and undergoing various kind of ventilatory treatments.…”
Section: Introductionmentioning
confidence: 99%